Effect of Long-term Fertilizer Experiment on Yield, Economics and Soil Fertility of a Vertisol under Soybean–Wheat Cropping System - Dwivedi, B. S.; Dixit, B. K.; Thakur, R. K.; Tripathi, P. N.; Tiwari, Rishikesh; Kurmi, Prashant (International Journal of Economic Plants, 2026)
The field study was conducted under the 50-year-old All India Coordinated Research Project on Long Term Fertilizer Experiment in a Vertisol at Jawaharlal Nehru Krishi Vishwavidyalaya, Jabalpur, Madhya Pradesh (INDIA) during 2021–22 to assess the productivity, soil fertility, and economics of a soybean–wheat cropping system. The experiment comprised eight treatments arranged in a randomized block design with four replications. The results indicated that the 100% NPK+5 t FYM ha-1 treatment produced the highest grain yield of soybean (2080 kg ha-1) and wheat (6150 kg ha-1); however, the lowest grain yield of soybean (825 kg ha-1) and wheat (1460 kg ha-1) was produced by the control plot. There were no significant differences in soil reaction (pH), and EC was noticed due to different treatments of fertilizers, either alone or in conjunction with organic manure. The soil organic carbon content had increased significantly from its initial value of 5.7 g kg-1 to attain a maximum value of 8.9 g kg-1 in the treatment comprised of 100% NPK along with organic manure. Further, the conjoint application of a balanced dose of inorganic fertilizers with organic manure resulted in superior post-harvest soil nutrient availability (N, P, K) compared to other treatment combinations. Economic analysis revealed the highest net returns (` 144,229 ha-1) and cost of cultivation (` 72,416 ha-1) under the integrated nutrient management treatment practices, yielding a favorable benefit–cost ratio (1.99) for the cropping system. Thus, the study confirms that the combined use of inorganic fertilizers with farmyard manure enhances system productivity and sustains the soil fertility of a Vertisol.